Analysis of Customer Relationship Management at Animation Studio - PT Jiwa Muda Cipta Indonesia in Yogyakarta - Haryagung Nugroho Yogyasworo; Rila Setyaningsih; Chandra Setya Bintara (Indonesian Journal of Business Analytics, 2024)
The role and function of Public Relations (PR) in carrying out tasks in the marketing sector of a digital service company, namely Animation Studio. Nowadays, managing relationships with customers is more familiarly known as Customer Relationship Management (CRM). In CRM management, a series of flows have been arranged as mentioned by Buttle, namely analysis, resource development and implementation. The data obtained in this research is the result of observation, documentation and interviews with Marketing and CEO while carrying out research at the Animation Studio. It was found that analyzes covering portfolio and customer intimacy had been run on a strong basis and implemented quite well. Likewise, the development of resources that have been designed by the CEO to develop the network and add value propositions has been carried out systematically according to procedures. As for the implementation of CRM in Animation Studio, although it is quite good, it still needs to be developed further in terms of the process to further perfect CRM within the company.